Students' Difficulties in Comprehending Narrative Text - Aulia Khoirunnisa; Estu Widodo (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Reading skill has been found to be one of difficult skills to achieve for many learners of English as a Foreign Language (EFL). Importantly, based on the preliminary study, narrative texts Â are deemed to be difficult.Â This study was conducted to investigate the studentsâ€™ difficulties in reading text at a private primary school in Batu, involving 29 ninth grade students in the academic year of 2018-2019 as the samples. Employing the purposive sampling method by which the best class was selected, the researcher used10-items of a closed-ended questionnaire to collect the data. In the analysis, some aspects of the narrative text such as words, structure, language feature, character, setting, plot, moral value, and point of view were highlighted. Consistently, narrative texts were found to be the most difficult text faced by students at school. According to the English teacher, students got the difficulties because of lack of vocabulary, the use of simple past tense, and the instruction to make sense of the moral values. Further, difficulties pertain to the effort to comprehend the structure, point of view, and the words.